Analisis Perawatan Mesin Injection dengan Metode RCM pada Perusahaan Manufaktur - Allysa Alsakina; Ade Momon (Universitas Indraprasta PGRI Jakarta, 2023)
At present, industrial companies, especially those engaged in the automotive manufacturing sector, are required to work effectively and efficiently. This research reviews the maintenance of mold machines, which are the main tools in the production process. The maintenance of this machine is very important. The problem that often occurs is in 550T injection engine which often experience a breakdown. Therefore, this research analyzes and plans more optimal maintenance by utilizing a system and applying the Reliability Centered Maintenance method. The research takes data from six engine components that are often damaged. Of the six components, the most critical ones are the clamping toggle, the nozzle, and the piston injection. The results of the research recommend maintenance inspections of the Finding Direction (FD) category that are performed daily, weekly, and monthly. In addition, in the Time Directed (TD) category, maintenance is provided based on a component replacement schedule in accordance with predetermined replacement intervals.